The use of wavy vortex generators in the cooling system to reduce the photovoltaic temperature rise - Gaguk Marausna; Erwan Eko Prasetiyo; Ferry Setiawan (Institute of Advanced Engineering and Science, 2023)
A solar panel will be exposed to sunlight when in use, which causes its temperature to increase. The performance of power production will be impacted if the solar panel's temperature conditions are too hot. High-temperature solar panels can reduce the amount of electrical energy generated. To prevent the temperature of the solar panels from rising too much, a cooling system is required. The proposed solution of this research is a cooling system for solar panels that makes use of heat transfer through water. The solar panels tested in this study have a tilt angle of 20 degrees. The cooling device has dimensions of 400 mm length, 278 mm width, and 20 mm height, with a wavy-type vortex generator positioned in the cooling device mounted on the underside of the solar panel. As a result of the heat flux applied to the top surface of the solar panel, it causes an increase in temperature. The resulting voltage and electric current are reduced. Computational simulations were carried out to determine the performance of the type of vortex generator used. At a cooling water flow rate of 200–600 ml/min, heat transfer with a vortex generator type B works optimally.